2012
DOI: 10.1016/j.ijgo.2012.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Detailed analysis of a randomized, multicenter, comparative trial of dienogest versus leuprolide acetate in endometriosis

Abstract: The analyses provide supportive evidence that the efficacy of DNG is equivalent to that of LA for treating endometriosis symptoms, with specific quality-of-life benefits and a favorable safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 24 publications
2
52
0
Order By: Relevance
“…DNG, which may be used for 1 year or more [1314], was used instead of a GnRH-a which has a limited duration of use, as it decreases bone mineral density. A comparative trial of DNG (2 mg/day) versus a GnRH-a [1516] concluded that DNG is as effective for the relief of pain associated with endometriosis [15]. The proportion of women free of pelvic pain and dysmenorrhea at 24 weeks was approximately 60% in both treatment arms: 82% in the DNG group and 90% in the GnRH-a group, respectively [16].…”
Section: Discussionmentioning
confidence: 99%
“…DNG, which may be used for 1 year or more [1314], was used instead of a GnRH-a which has a limited duration of use, as it decreases bone mineral density. A comparative trial of DNG (2 mg/day) versus a GnRH-a [1516] concluded that DNG is as effective for the relief of pain associated with endometriosis [15]. The proportion of women free of pelvic pain and dysmenorrhea at 24 weeks was approximately 60% in both treatment arms: 82% in the DNG group and 90% in the GnRH-a group, respectively [16].…”
Section: Discussionmentioning
confidence: 99%
“…of articlesPublication year(s)Total no. of patientsaTreatment duration, moStudy typeFunding sourcebDanazol31982–19984814 to ≥6Prospective cohort study (n = 2) 9, 10; retrospective study (n = 1) (11)Nonindustry (n = 3)Gestrinone319957026RCT (n = 3) 12, 13, 14Nonindustry (n = 3)Mifepristone120162706RCT (n = 1) (15)Nonindustry (n = 1)GnRH agonists141988–20002,7833–6RCT (n = 12) 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27; prospective cohort study (n = 2) 28, 29Industry (n = 8); partial industry (n = 3); nonindustry (n = 3)GnRH agonists plus add-back therapy41998–20167385–12RCT (n = 3) 30, 31, 32; prospective cohort study (n = 1) (33)Industry (n = 1); partial industry (n = 1); nonindustry (n = 2)Progestins142000–20162,6943–12RCT (n = 8) 34, 35, 36, 37, 38, 39, 40, 41; prospective cohort study (n = 5) 42, 43, 44, 45, 46; retrospective study (n = 1) (47)Industry (n = 7); partial industry (n = 2); nonindustry (n = 5)CHCs…”
Section: Resultsmentioning
confidence: 99%
“…[32][33][34] Dienogest has a strong endometrial affinity and it may directly decrease growth, neoangiogenesis, and proliferation of endometriotic lesions. [7][8][9][10][11][12][13][14] In our study, DNG was used at doses sufficient to perform this clinical effect. The cumulative exposure per cycle to DNG was about 2.2 mg/d, which is comparable to that approved for the treatment of endometriosis (2 mg/d).…”
Section: Resultsmentioning
confidence: 99%
“…The cumulative exposure per cycle to DNG was about 2.2 mg/d, which is comparable to that approved for the treatment of endometriosis (2 mg/d). [8][9][10][11][12] It is likely that the circulating levels of E2 induced by E2V/ DNG, with values ranging between 60 and 90 pg/mL, 32 were not capable to counteract the potent effect of DNG on endometriotic lesions. Large randomized clinical comparative trials on this topic are mandatory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation